Possible Fruit Protein Effects on Primate Communities in Madagascar and the Neotropics - Ganzhorn, Jörg U. (2009)
Background: The ecological factors contributing to the evolution of tropical vertebrate communities are still poorly understood. Primate communities of the tropical Americas have fewer folivorous but more frugivorous genera than tropical regions of the Old World and especially many more frugivorous genera than Madagascar. Reasons for this phenomenon are largely unexplored. We developed the hypothesis that Neotropical fruits have higher protein concentrations than fruits from Madagascar and that the higher representation of frugivorous genera in the Neotropics is linked to high protein concentrations in fruits. Low fruit protein concentrations in Madagascar would restrict the evolution of frugivores in Malagasy communities. Methodology/Principal Findings: We reviewed the literature for nitrogen concentrations in fruits from the Neotropics and from Madagascar, and analyzed fruits from an additional six sites in the Neotropics and six sites in Madagascar. Fruits from the Neotropical sites contain significantly more nitrogen than fruits from the Madagascar sites. Nitrogen concentrations in New World fruits are above the concentrations to satisfy nitrogen requirements of primates, while they are at the lower end or below the concentrations to cover primate protein needs in Madagascar. Conclusions/Significance: Fruits at most sites in the Neotropics contain enough protein to satisfy the protein needs of primates. Thus, selection pressure to develop new adaptations for foods that are difficult to digest (such as leaves) may have been lower in the Neotropics than in Madagascar. The low nitrogen concentrations in fruits from Madagascar may contribute to the almost complete absence of frugivorous primate species on this island.